2016
DOI: 10.3390/ijms17060803
|View full text |Cite
|
Sign up to set email alerts
|

NAFLD and NASH in HCV Infection: Prevalence and Significance in Hepatic and Extrahepatic Manifestations

Abstract: The aim of this paper is to review and up to date the prevalence of hepatitis C virus (HCV)-associated non-alcoholic fatty liver disease (NAFLD) and non-alcoholic steatohepatitis (NASH) and their significance in both accelerating progression of HCV-related liver disease and development of HCV-associated extrahepatic diseases. The reported mean prevalence of HCV-related NAFLD was 55%, whereas NASH was reported in 4%–10% of cases. HCV genotype 3 directly induces fatty liver deposition, namely “viral steatosis” a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(112 citation statements)
references
References 88 publications
(136 reference statements)
5
89
0
6
Order By: Relevance
“…In our study patients with diabetes mellitus had slightly higher baseline liver stiffness, and we found that we can expect to see increasing liver stiffness during the course of the 12 weeks DAA treatment, but this does not hinder the eventual regression in liver fibrosis by 12 weeks post-treatment (p=0.272), which occurs at a similar rate as that seen in patients without diabetes mellitus. The cumulated risk for advanced fibrosis is even higher in patients who, on top of glucose abnormalities, also associate fatty liver disease, a condition which has been reported to have prevalences as high as 55% in patients with HCV infection (19), and in our study was present in 72.7% of patients, albeit only 13.7% presented advanced steatosis. In this context, a personalized medical nutrition regimen becomes a powerful instrument in preventing and/or treating fatty liver disease in patients with HCV infection (20).…”
Section: Discussionsupporting
confidence: 39%
“…In our study patients with diabetes mellitus had slightly higher baseline liver stiffness, and we found that we can expect to see increasing liver stiffness during the course of the 12 weeks DAA treatment, but this does not hinder the eventual regression in liver fibrosis by 12 weeks post-treatment (p=0.272), which occurs at a similar rate as that seen in patients without diabetes mellitus. The cumulated risk for advanced fibrosis is even higher in patients who, on top of glucose abnormalities, also associate fatty liver disease, a condition which has been reported to have prevalences as high as 55% in patients with HCV infection (19), and in our study was present in 72.7% of patients, albeit only 13.7% presented advanced steatosis. In this context, a personalized medical nutrition regimen becomes a powerful instrument in preventing and/or treating fatty liver disease in patients with HCV infection (20).…”
Section: Discussionsupporting
confidence: 39%
“…These differences are explained by the Many authors consider that, despite the fact that insulin resistance is the common etiological link, the prevalence of MeS in HCV infection is similar to that of the general population (16). Consequently, in a study by Lonardo, the prevalence of MeS in patients with HCV was 4.1%, similar to that of the control group and reduced compared with the prevalence in NAFLD (27.9%) (17).…”
Section: Discussionmentioning
confidence: 97%
“…Idült C-vírus hepatitisben szenvedő betegekben körülbelül 50%-ban (40-88%) mutatható ki a máj változó mértékű elzsírosodása, amely mintegy 2,5-szerese a más kórokú májbetegségben ész-leltnek (hepatitis B: 26%, autoimmun májbetegség: 17%) [29,30].…”
Section: Inzulinrezisztencia Diabetes Mellitusunclassified